2015
DOI: 10.1038/srep11549
|View full text |Cite
|
Sign up to set email alerts
|

Integrative miRNA and Gene Expression Profiling Analysis of Human Quiescent Hepatic Stellate Cells

Abstract: Unveiling the regulatory pathways maintaining hepatic stellate cells (HSC) in a quiescent (q) phenotype is essential to develop new therapeutic strategies to treat fibrogenic diseases. To uncover the miRNA-mRNA regulatory interactions in qHSCs, HSCs were FACS-sorted from healthy livers and activated HSCs (aHSCs) were generated in vitro. MiRNA Taqman array analysis showed HSCs expressed a low number of miRNAs (n = 259), from which 47 were down-regulated and 212 up-regulated upon activation. Computational integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 33 publications
5
65
0
Order By: Relevance
“…Currently, there are no approved antifibrotic drugs for the treatment of liver fibrosis. Recent studies on lung, kidney, heart, and liver fibrosis have reported that blocking miR-21 exerts antifibrogenic effects (12)(13)(14)(22)(23)(24)(25) and that miR-21 may therefore represent a potential therapeutic target. However, studies using both genetic knockout as well as pharmacologic approaches have refuted some of these findings, (15,45,46) thus rendering the contribution of miR-21 to fibrosis and its potential use as a therapeutic target controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no approved antifibrotic drugs for the treatment of liver fibrosis. Recent studies on lung, kidney, heart, and liver fibrosis have reported that blocking miR-21 exerts antifibrogenic effects (12)(13)(14)(22)(23)(24)(25) and that miR-21 may therefore represent a potential therapeutic target. However, studies using both genetic knockout as well as pharmacologic approaches have refuted some of these findings, (15,45,46) thus rendering the contribution of miR-21 to fibrosis and its potential use as a therapeutic target controversial.…”
Section: Discussionmentioning
confidence: 99%
“…(18)(19)(20) In the liver, miR-21 is believed to regulate a wide range of injury responses, including hepatocyte proliferation, (21) biliary hyperplasia, (22) carcinogenesis, (23) and liver fibrosis. (22)(23)(24)(25) Here, we identified miR-21 as the microRNA with the highest induction in HSCs in multiple models of HSC activation. However, two diferent lines of miR-21 knockout mice as well as pharmacologic suppression of miR-21 expression did not reveal a role for this microRNA in HSC activation or liver fibrosis.…”
mentioning
confidence: 95%
“…Both paired miRNA and mRNA expression profiles were used for the integrative analysis by MiRComb package, as previously described 18. Functional analysis of significant dysregulated gene targets was performed with Ingenuity Pathway Analysis (Qiagen; Red Wood, California, USA).…”
Section: Methodsmentioning
confidence: 99%
“…High-throughput miRNA profiling and other technologies have identified pro-fibrogenic miRNAs over-expressed in activated HSCs, including miR-9a-5p, miR-17-5p, miR-21, miR-27, miR-31, miR-33a, miR-34a/c, miR-125, miR-126, miR-130a/b, miR-181b, miR-214-5p, miR-195, miR-199a/b, miR-221, and miR-222, each of which induces proliferation, collagen secretion, and/or migration via a variety of pathways, and anti-fibrotic miRNAs, including miR-16, miR-19b, miR-29, miR-30, miR-101, miR-122, miR-133a, miR-144, miR-146a, miR-150, miR-155, miR-192, miR-195, miR-335, miR-454, and miR-483, although direction of change could depend on biological and/or experimental contexts [267269]. miR-378 was recently shown to limit HSC activation by suppressing Gli3 [270].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%